TRADISI SABUNG AYAM DI MASYARAKAT TALANG MAMAK DI DESA TALANG SUNGAI LIMAU KECAMATAN RAKIT KULIM INDRAGIRI HULU - Andani, Yeni Dewi; Jalil, Ashaluddin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Sabung ayam tradition is one of tradition from Talang Mamak tribe at Talang Sungai Limau village. This tradition has been existed from years ago and it was inheritedfrom past generation. This game is played due to the belief of Talang Mamak people that this game is the order from God and should be preserved. This game will be conducted to celebrate a baby born, wedding reception, or somebody’s death. In this research, the researcher was trying to find out the meaning of Sabung Ayam in commemorating a death. This research was conducted by qualitative method with purposive sampling technique that consist of batin, mangku and monti of Talang Mamak tribe at Talang Sungai Limau village. The meaning of sabung to Talang Mamak tribe is to help somebody who has something in purpose by giving anything He/She has. It can be money, chicken, egg, rice, etc. Sabung ayam has manifest funcition as entertainment, education and buid solidarity. However, it also has laten function as gambling preservation. Keywords : tradition, sabung ayam meaning, Talang mamak tribe